Applied data science for researching innovation, impacting capital attraction and economic development in Vietnam - Hien, Lam Thanh; Tam, Phan Thanh (International Journal of Innovative Research and Scientific Studies, 2025)
The COVID-19 pandemic has significantly disrupted investment activities and economic operations worldwide, including in Ho Chi Minh City (HCMC), Vietnam. Due to restricted mobility and heightened uncertainty, domestic and international investors have reduced their investment commitments. Therefore, the research aims to identify key elements influencing HCMC’s capital attraction and economic development in Vietnam and provide evidence-based policy recommendations to enhance the city’s investment appeal and drive sustainable economic development. The authors employed a straightforward and random survey methodology to gather data from a sample of 700 HCMC investors by applying structural equation modeling (SEM). The study explored key factors affecting capital attraction in HCMC and its influence on economic development with a significance level of 1.0 percent. The findings and model can serve as a reference for other emerging cities worldwide aiming to attract foreign investment and accelerate economic development, particularly during crisis recovery. Finally, the study proposes suitable policy recommendations for economic development based on revising and modernizing laws related to foreign investment to align with international standards while ensuring compatibility with Vietnamese legal frameworks. It encourages the adoption of innovative policies and investment promotion mechanisms to attract global brands.